Reconstruction of the Historical Landscape and Memory of Places. A Defense Project in the Southern Territory of Cagliari as described in a 1707 Report - Andrea Pirinu; Marcello Schirru (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2022)
On 1st August, 1707, the Patrimonial Council of the Kingdom of Sardinia approved the contents of the report drawn up by Don Manuel Bellejo, Prince of Tapia, regarding the interventions to be carried out in the defensive works ion land to the south of Cagliari. The so-called War of Succession to the Throne of Spain, fought by land, sea and on several continents, put a strain on the military sector of the various states. The port cities assumed strategic importance, as evidenced by the investments made in strengthening the strongholds of the Kingdom. The danger of invasion of Sardinia was  evident in the report of Don Manuel, who identified a weak point of Cagliari in the territory between the promontory of Sant’Elia and the Villanova district. With an ideal bird’s eye-view , Bellejo accompanies the reader through the anti-invasion garrisons, ringing places, natural features, and  paths, illustrating the defensive works inspected or necessary. The wealth of details allows to relocate the ancient garrisons on historical and current cartography and to reconstruct the conformation of the territory. For this purpose, the maps and military projects produced between the 16th and 18th centuries are fundamental aids. The comparison between ancient maps and today’s aerial photogrammetry provides solid tools for the study of the document, which opens an interesting window on the Cagliari of the time: a short, but intense historical phase that narrowly precedes the great transformations of the Savoy era.